Wayang (Puppet) Character Transformation Model In Augmented Reality - I Putu Ardiyasa (Institut Seni Indonesia Denpasar, 2020)
The art of wayang that thrives, are dynamic and always adapt to the times need to consider the regeneration of puppet show audiences. The presence of technology has changed the audience’s paradigm of verbal performances into visual performances. This wayang character transformation model is an offering of AR application-based art products that aim to become a medium for introducing wayang art from an early age and in various rooms. This study develops an Augmented Reality application. Data were collected using data collection methods in the form of observation, interviews and simple questionnaires and documentation studies. The results showed that there are two models, namely, the Tri Sandi and the Waterfall model. This modeling found the form of a puppet character recognition application product that contains plot, tetikesa, antawacana (speech presentation style), discourse, stage and melody.